Green Synthesis, Characterization and Antifungal Activity of Silver Nanoparticles Using Stems and Flowers of Felty Germander - Ghojavand, Solmaz; Madani, Mahboobeh; Karimi, Javad (Journal of inorganic and organometallic polymers and materials, 2020)
Green synthesis of silver nanoparticles (AgNPs) using a number of biological agents such as extracts from various parts of the plants have garnered remarkable attention recently. The aim of the study was a green synthesis of AgNPs using stems and flowers of Felty germander ( Teucrium polium L.). After collection and preparation of the aqueous extract, production of AgNPs was performed. In the study, effect of parameters including AgNO 3 concentration (1, 5, 10, 15, 20, 25, and 50 mM), aqueous extract (100 µl, 150 µl, 300 µl, 600 µl and 900 µl), pH value (between 0 and 14), incubation time (5, 10, 15, 20, 25, and 30 min), and temperature (30 °C, 60 °C, and 90 °C) were investigated in the synthesis of AgNPs. The sufficient production was achieved at the room temperature (30 °C), duration of 15 min, pH of 6 and concentration of 7.5 mM of AgNO 3 . Finally, the antifungal activity of these nanoparticles was also studied on Fusarium oxysporum by colony formation assay. The production of AgNPs was identified by an absorption peak at approximately 450 nm using UV–Visible spectroscopy. According to XRD, DSL, FESEM, and PSA results and analysis of SEM, nanoparticles have almost spherical shape and size of 10 to 100 nm. The SEM images also revealed that the prepared AgNPs are particles with no agglomeration. Furthermore, the TEM images exhibited that the AgNPs were well dispersed and there was no evident aggregation. Absorption peaks at 3391.55, 2917.00, 2848.83, 1640.15, 1384.65, 1243.37, 1069.07 and 614.54 cm −1 were observed for the AgNPs using FTIR analysis. On the other hand, the antifungal analysis revealed that these AgNPs have antifungal activity. For the first time, the biosynthesis of AgNPs was successfully performed using the aqueous extract of Felty germander which is a rapid, inexpensive and safe approach. Furthermore, the resulting AgNPs has antifungal activity.